Evaluation of the hepatoprotective and nephroprotective properties of bael fruit extract against carbon tetrachloride-induced toxicity in rats - Garg, Deepak; Sharma, Amit; Pragi; Kumar , Varun (Creative Pharma Assent, 2024)
Background: Bael is well-known for its antibacterial properties. Aqueous fruit extracts have also been shown to have hepatoprotective properties; the nephroprotective and hepatoprotective properties of Ethanolic extracts have not yet been tested. Objective: To evaluate the hepatoprotective and nephroprotective activities of Bael against CCl4-induced toxicity in rats. Methods: Two dosages of Bael's Ethanolic extract (100 and 200 mg/kg/day) were compared with 100 mg/kg of silymarin. Histopathologic alterations of the liver and kidney, as well as biochemical blood parameters such as bilirubin, urea, uric acid, total protein and creatinine, alkaline phosphatase (ALP), alanine aminotransferase (ALT), were examined and assessed. Results: Bael was more successful in lowering high levels of urea, creatinine, ALT, AST, and ALP when he used a 200 mg/kg/day methanol extract. According to the histopathologic assessment, Bael lessened the CCl4-induced hepatic and renal necrosis. The more significant dose resulted in reductions in AST, ALT, GGT, ALP, and bilirubin of 45,25, 52,36, and 16%, respectively. Ethanolic extract 200 mg/kg/day also shows a reduction in elevated levels of Creatinine, Urea, Uric Acid, and Total Protein by 57%, 52%, 34%, and 9%, respectively. Conclusion: There were established hepatoprotective and nephroprotective effects of the Bael fruit methanol extract, with 200 mg/kg/day being the most beneficial dose. This provides scientific proof that medicinal herbs like Bael can be used to treat renal and liver diseases.